ANALISIS KINERJA KEUANGAN PADA KOPERASI KARYAWAN PT. BANK SYARIAH MANDIRI - Sulistyowati, Yuni; Pramudita, Natasya Putri; Amalia, Dina; Rohmah, Nur; Indriani, Fina; Hulu, Winis Trilian; Sabil, Sabil (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
This research was conducted to understand the financial performance of the Employee Cooperative of PT. Bank Syariah Mandiri. The type used in this study was secondary data involving various sources such as collecting data taken from the financial reports of the Employee Cooperative of PT. Bank Syariah Mandiri. This research was a quantitative analysis type with non-statistical research methods. Overall, the financial condition of the cooperative tended to show a decline in health from 2020 to 2021, especially in terms of liquidity and profitability. This could be attributed to underoptimized assets, such as cash or receivables not managed and utilized effectively to generate additional income, for example, for investment or to use cash to expand business operations. Based on the analysis of the financial performance of the employee cooperative of PT. Bank Syariah Mandiri from 2020 to 2021, the cooperative should have improved efficiency in the use of current assets to increase liquidity ratios, enhanced profitability through strategies that could increase income, and also maintained healthy debt ratios (DAR and DER) by managing debt more effectively so that the Employee Cooperative of PT. Bank Syariah Mandiri could have improved financial conditions and ensured better operational sustainability in the future.